Photographic manipulation and journalistic media credibility through photography - Martínez García, Geraldine (2019)
This paper aims to determine how photographic manipulation relates to the credibility of journalistic media through the photograph published in Los Angeles Times referred to the Second Gulf War, 2003. This research has a non-experimental crosscutting design, applicative type with descriptive, correlational and comparative levels, as well as inductive, deductive, analytical, statistical, and hermeneutic method. By units of analysis and population samples (taken from students in Lima and New York City) the general hypothesis, where photographic manipulation is significantly related to the credibility of journalistic media through the photograph published in Los Angeles Times referred to the Second Gulf War in 2003, was confirmed.